Korelasi Fungsi Kognitif dengan Kemampuan Menamai pada Pasien Post Stroke di Wonosobo - Zahrani, Dewi; Romey Daulas Mangunsong, Roy (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: Stroke can cause disability in sensory, motor and even cognitive functions, if left untreated. Having cognitive abilities, a person uses his thinking tools to observe, relate, assess, and consider events or events in order to solve problems as effectively and efficiently as possible in achieving goals. Cognitive function is a mental capacity that includes attention, linguistic skills, memory, visuospatial abilities, conceptual abilities, and intelligence. Objectives: To determine the correlation between cognitive function and naming ability in post-stroke patients in Wonosobo. Methods: The type of research used in this research is quantitative with a research design, namely correlational research. In taking samples using a purposive sampling technique as many as 30 Post Stroke patients. Bivariate analysis was used to analyze the relationship between cognitive function and naming ability in Post Stroke patients in Wonosobo using the Spearman Rank test. The research instruments used were the Mini Mental State Examination (MMSE) test and the TADIR test for word level naming abilities. Results: Testing the influence of the statistical value of the Spearman Rank Test, the Correlation Coefficient (r) value obtained was 0.829, which means the two variables have a moderate level of correlation strength. Significant (p) is shown in the Approx column. Sig with a result of 0.000 then the p value <0.05. Conclusion: There is a positive correlation between cognitive function and naming ability in Post Stroke patients in Wonosobo Keywords: Cognitive Function, Naming Ability, Post Stroke